Technological innovations and sustainable strategies for advancing electric vehicle performance and market integration - Priya Ranjan Satpathy; Vigna Kumaran Ramachandaramurthy; Thurga R. Radha Krishnan; Sanjeevikumar Padmanaban (Energy Strategy Reviews)
Electric vehicles (EVs) are transforming the transportation landscape through rapid technological advancements and a growing focus on sustainability. This review offers a structured, multi-dimensional synthesis of the EV ecosystem, examining its historical evolution, core technologies, market trends, and policy influences. Key developments in battery chemistry, charging infrastructure, power electronics, and thermal management are critically analyzed for their impact on performance, scalability, and integration. The paper highlights emerging trends such as AI-driven energy management, vehicle-to-grid (V2G) systems, and the role of renewable energy sources in enabling bidirectional, grid-responsive EV operations. Unlike previous reviews, this study utilizes structured comparative methods to critically assess technologies and adoption pathways, incorporating SWOT analyses, maturity-scalability evaluations, and future readiness mapping. The review addresses systemic challenges, including battery recycling, hydrogen fuel integration, cybersecurity, and infrastructure interoperability. Insights are categorized across six thematic domains to reveal current gaps, interdisciplinary dependencies, and opportunities for innovation. The paper concludes with strategic recommendations to assist researchers, policymakers, and industry stakeholders in accelerating the transition to next-generation, intelligent EV systems.